Evaluation and development of a bone age assessment method in patients with Down syndrome - Moraes, Michelle Bianchi de; Moraes, Mari Eli Leoneli de; Raldi, Fernando Vagner; Ragone, Simone Maria Guimarães; Holleben, Déborah (Brazilian Dental Science, 2012)
This study evaluated the applicability of the method developed by Caldas to measure vertebral bone age for Brazilians suffering from Down syndrome. A database comprised of 57 case records of individuals with this syndrome, both male and female, with age ranging between 5 and 18 years, was assessed. These records had lateral cefalometric radiographies and radiographies of hand and wrist, being all obtained on the same date. Also, 48 records of individuals not suffering from Down syndrome were assessed. For the hand and wrist radiographies the Tanner and Whitehouse (TW3) method was used, and bone age was obtained. The Caldas method was employed on the lateral cefalometric radiographies in order to obtain the vertebral bone age. From the information about the bone age, vertebral bone age and chronological age, the Wilcoxon test was used to compare all the ages in pairs. There was a statistically significant difference between the three ages mentioned above for both male and female control group and female Down syndrome group. Therefore, this method was only suitable for Down syndrome male individuals. Based on the results, a formula to obtain the bone age for Down syndrome individuals was developed.